(untitled) - Simon, Coco; Lâopez, Manuela; 1985- (Simon Spotlight, 2024)
"Cupcake Club founder Katie Brown's stepsister Emily enters a baking contest at her new school and discovers her own way to bake"--
Keywords: Contests; Fiction; Baking; Fiction; Schools; Family life; Stepsisters; Fiction; Fiction; Fiction; Friendship; Fiction; Families; Juvenile fiction; Juvenile fiction; Contests; Juvenile fiction; Baking; Friendship; Schools; Juvenile fiction; Stepsisters; Juvenile fiction; Juvenile fiction